Reclaiming the great world house : the global vision of Martin Luther King Jr. - Baldwin, Lewis V., 1949-; Crawford, Vicki L.; Franklin, Robert M.; Anderson, Victor; Delgado, Teresa; Rivers, Larry; Degregory, Crystal A.; Selby, Gary S.e contributor; Fluker, Walter E. (Morehouse College King Collection series on civil & human rights., 2019)
"Reclaiming the Great World House in the 21st Century: Cross-Disciplinary Explorations of the Vision of Martin Luther King, Jr., does just that. Established and emerging scholars explore Martin Luther King, Jr.'s global vision and his lasting relevance to a globalized rights culture. The editors further explain that this edited collection looks at: King afresh in his own historical context, while also refocusing his legacy of ideas and social praxis in broader directions for today and tomorrow. Employing King's metaphor of "the great world house," with major attention to racism, poverty, and war - or what he called 'the evil triumvirate"--The focus is on King's appraisal of and approach to the global-human struggle in the 1950s and 60s, and on the extent to which his social witness and praxis takes on new hues and pertinence not only in the ongoing struggles against racism, poverty and economic injustice, and violence and human destruction, but also in the mounting efforts to eliminate problems such sexism, homophobia, and religious bigotry and intolerance from the global landscape. The conclusion is that King's ideas and models of social protest are not only alive but also growing in vitality and popularity in the 21st century, especially as humans worldwide are struggling daily with the lingering, antiquated thinking and behavior around race and ethnicity, the widening gap between "the haves" and "the have-nots," the mounting cycles of violence, torture, and terrorism, and the frustrating and growing chasms resulting from religious pluralism and the subordination and marginalization of certain sectors of the human family based on gender and sexuality"--